Strong base- or acid-mediated chemoselectivity shifts in the synthesis of 2H-chromene or coumarin derivatives from common Baylis-Hillman adducts. Issue 29 (22nd July 2015) - Faridoon,; Olomola, Temitope O.; Tukulula, Matshawandile; Klein, Rosalyn.; Kaye, Perry T.
Abstract: Reaction of tert -butyl 3-(2-hydroxyphenyl)-2-methylenepropanoate esters with aqueous KOH provides convenient and chemoselective one-pot access to 2 H -chromene-3-carboxylic acids, the overall transformation involving tandem conjugate addition, hydrolysis and elimination steps. The methodology complements the chemoselective, acid-catalysed route to 3-substituted coumarins from the same substrates by switching the regioselectivity of cyclisation. Graphical abstract: